Impact of Women's Role in Improving Family Welfare in Bantul Yogyakarta District Using the CIBEST Model - Diah Arminingsih (JURNAL MUAMALAT INDONESIA - JMI, 2023)
The GBHN states that women have rights, responsibilities and have the opportunity to fully participate in development. So that as a consequence in the perspective of national interests, women must be involved and involved in solving national problems. Women's empowerment is an indicator of increasing welfare. If women are empowered economically, intellectually and spiritually, it will be very effective for the development of society and the nation. The purpose of this study was to determine the impact of women's role in improving family welfare from an Islamic perspective. The research design uses mixed methods through two stages which are carried out at almost the same time. Data analysis techniques in this study used two approaches, namely qualitative and quantitative approaches. In the qualitative approach, the data is obtained from data reduction, while the quantitative approach uses descriptive analysis. To determine the level of women's welfare using the CIBEST model welfare measurement tool. The results of the research found that the role of women is able to improve welfare through empowerment programs. The effect of the empowerment program on welfare can be seen in the average difference (mean diference) welfare before participating in the empowerment program and after participating in the empowerment program from an average welfare of 5.14 to an average of 5.69. Through the analysis of the CIBEST approach, the role of women in improving family welfare is illustrated by changes in the index in a better direction, namely changes in the material poverty index decreased by 41.9%, changes in the spiritual poverty index have the same index, namely 0 (zero), changes in the absolute poverty index decreased by 1%, and changes in the welfare index increased by 42.9%. Keywords: Role, Women, Empowerment, CIBEST